Al-Ghâlibûn Le Hezbollah et la mise en récit de la « société de la résistance » au Liban - Erminia Chiara Calabrese (Revue des Mondes Musulmans et de la Méditerranée)
After the liberation of South Lebanon in 2000, the Hezbollah party leadership understood the importance of audiovisual tools over movie-going, and used television as their key device to influence public opinion and mobilize the Lebanese Shiite community to join what the party calls the “society of resistance”. Accordingly, the Al-Ghâlibûn [The Victorious] series was produced, which traces the early years of the Islamic Resistance (1982-1985) against the Israeli occupation. In this article we examined the socio-political and symbolic dimension of the series which contributes to the perpetuation of the Hezbollah’s unifying myths. Several issues raised in various episodes introduce an alternative lifestyle proposed by the party where resistance against the Israeli occupation became a mission and a cause.